A PROFILE OF TUBERCULOSIS CASES AMONG HIV POSITIVE PATIENTS IN NAVI MUMBAI.: Life Sciences-Microbiology - DR.HARAPRIYA KAR; DR. CHITRA (BHAT) PAI; DR.REVATI SHARMA; MINAKSHI BHATTACHARJEE; DR. SAMIR PACHPUTE (International Journal of Life Science and Pharma Research, 2022)
The purpose of the study was to find the prevalence of extra pulmonary and pulmonary TB in the area of Navi Mumbai 113 adult TB patients having confirmed HIV sero-positivity were screened for the current study. The diagnosis of TB was based on clinical impression and relevant investigations including CBC with ESR, Mantoux test, Chest X-ray, USG Abdomen and Pelvis, sputum smear AFB examination in case of pulmonary symptoms, Fluid analysis and studies Bac- T Alert methods, Fine needle aspiration cyto (FNAC), Real-time PCR (Light cycler Roche 480) and CT scan. Prevalence of tuberculosis in HIV -positive patients in this study was (43.3%). Extra pulmonary TB (61%) was found to be more common than pulmonary TB (39%). There is a high prevalence of extra pulmonary TB in HIV patients in this area of Navi Mumbai. The study also inferred that patients with relatively high CD4 counts should be essentially screened for tuberculosis.